1985
DOI: 10.1152/ajpheart.1985.248.1.h151
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of autonomic function in humans by heart rate spectral analysis

Abstract: Spectral analysis of spontaneous heart rate fluctuations were assessed by use of autonomic blocking agents and changes in posture. Low-frequency fluctuations (below 0.12 Hz) in the supine position are mediated entirely by the parasympathetic nervous system. On standing, the low-frequency fluctuations increase and are jointly mediated by the sympathetic and parasympathetic nervous systems. High-frequency fluctuations, at the respiratory frequency, are decreased by standing and are mediated solely by the parasym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

52
1,558
6
44

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,901 publications
(1,660 citation statements)
references
References 6 publications
52
1,558
6
44
Order By: Relevance
“…During stationary resting conditions, different maneuvers, such as controlled breathing, muscarinic blockade with atropine or cold face immersion, have shown that the high frequency component of HRV, as well as timedomain parameter RMSSD (in large part), are predominantly the result of fluctuations in vagal-cardiac nerve activity (Akselrod et al 1981;Berntson et al 1993;Cacioppo et al 1994;Pomeranz et al 1985;Task Force, 1996). Therefore, high frequency power (HFP) may provide an index of vagal activity, but the potential influence of respiration on RSA must be considered, because the rate, and also slightly the depth, of breathing has been found to affect RSA (Akselrod et al 1981;Task Force, 1996).…”
Section: Frequency Domain Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…During stationary resting conditions, different maneuvers, such as controlled breathing, muscarinic blockade with atropine or cold face immersion, have shown that the high frequency component of HRV, as well as timedomain parameter RMSSD (in large part), are predominantly the result of fluctuations in vagal-cardiac nerve activity (Akselrod et al 1981;Berntson et al 1993;Cacioppo et al 1994;Pomeranz et al 1985;Task Force, 1996). Therefore, high frequency power (HFP) may provide an index of vagal activity, but the potential influence of respiration on RSA must be considered, because the rate, and also slightly the depth, of breathing has been found to affect RSA (Akselrod et al 1981;Task Force, 1996).…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…LFP, with a center frequency of about 0.1 Hz, appears to reflect a baroreflex resonance frequency (Berntson et al 1997;Pomeranz et al 1985). It has been suggested to reflect sympathetic outflow, especially when expressed in normalized units (nu) (Malliani et al 1994).…”
Section: Frequency Domain Analysismentioning
confidence: 99%
“…156 ± 158 One technique used in the determination of HRV, referred to as power spectral analysis, produces spectra of heart rate oscillations in the frequency domain by mathematically transforming a series of sequential RRI into speci®c frequency components (high frequency: HF RRI , and low frequency: LF RRI ). The HF RRI component of HRV is believed to represent solely e erent vagal in¯uences, 159 whereas interpretation of the LF RRI component is more controversial. The general consensus, however, is that this component estimates cardiac sympathetic modulation.…”
Section: Hrv and Bpv Analysismentioning
confidence: 99%
“…When applied to the heart rate, power spectral analysis allows for the detection of the low frequency component (LF, marker of sympathetic activity), and of the high frequency components (HF, related to the respiratory activity, which is mediated by the vagus nerve). [11][12][13][14] The ratio between the LF and HF components (LF/HF) is, therefore, an index of the sympatho-vagal balance. 15 …”
Section: Introductionmentioning
confidence: 99%